Mechanoluminescence and Deformation Bleaching in Colored Alkali Halide Crystals - Roy, R.S. (Asian Journal of Chemistry, 2010)
The present paper reports the mechanoluminescence (ML) and deformation bleaching of a colouration in coloured alkali halide crystals. As the F-centre electrons captured by moving dislocations are picked up by holes, deep traps and other compatible traps, so deformation bleaching occurs. Simultaneously radiative recombination of dislocation captured electrons with the holes gives rise to the mechanoluminescence. Expressions have been derived for the strain dependence of the density of colour centres is deformed crystals and for the number of colour centres bleached. So far as strain, temperature, density of colour centres, Ea and volume dependence are concerned, there exists a correlation between the deformation bleaching and mL in coloured alkali halide crystals. From the strain dependence of the density of colour centres in deformed crystals, the value of coefficient of deformation bleaching 0 is found to be 1.929 and 1.990 for KCI and KBr crystals respectively. The value of (D + χ) as determined from the strain dependence of the ML intensity is found to be 2.59 and 3.69 for KCI and KBr crystals respectively. This gives the value of coefficient of deformation generated compatible traps χ to be 0.68 and 1.69 for KCI and KBr crystals respectively.